Optimisation of fibre-matrix interface in carbon fibre reinforced light metals via liquid phase impregnation coatings. (2017) - Jiménez, M.; Gadow, R.; Weichand, P.
Fibre reinforced metals are a potential alternative to replace steel components in the automotive industry due to their enhanced specific strength. Nevertheless, state of the art metal matrix composites (MMC) are reinforced by expensive ceramic fibres, since the shaping and consolidation conditions by the classic manufacturing routes are quite severe in terms of thermal load and fibre-matrix chemical compatibility requirements. The semi-solid forming and shaping (SSFS) route, based on a densification process at the thixotropic temperature range of the employed alloy, is a promising alternative that enables the implementation of inexpensive high tenacity carbon fibres due to the reduced processing temperature. In this paper interfaces in carbon fibre reinforced AlSi6 are modified by liquid phase impregnation (LPI) fibre coatings, improving the strength and strain to failure of composites by 45 % compared to reference materials. The fractographic analysis shows the reduction of brittle failure and the formation of pull-out phenomena in composites based on coated fibres.